Correlation between visceral adiposity index and erectile dysfunction in American adult males: a cross-sectional study based on NHANES - Xu, Mingming; Zhou, Hang; Zhang, Ruihao; Pan, Yang; Liu, Xiaoqiang (Frontiers in Endocrinology, 2023)
Background: The risk of visceral obesity on erectile function has recently attracted much attention. The visceral adiposity index (VAI) is a brief and reliable indicator of visceral obesity measurement. Nevertheless, the association between VAI and erectile dysfunction (ED) is not completely clarified. Methods: Data from NHANES 2001-2004 were enrolled in this study. Erectile function was assessed by a database-self-administered questionnaire. VAI was calculated with body mass index (BMI), waist circumference (WC), triglyceride (TG), and high-density lipoprotein (HDL) cholesterol. The weighted logistic regression model was performed to evaluate the association between VAI and ED.Results: Ultimately, 3380 participants were enrolled in the study, including 900 with ED and 2480 without ED. Compared to participants without ED, those with ED generally had higher levels of VAI (1.76 vs. 1.53). The weighted logistic regression analyses demonstrated increased odds of developing ED in participants within the 4th quartile (Q4) of VAI compared to the 1st quartile (Q1) of VAI (OR = 2.023; 95% CI, 1.534-2.669; P < 0.001). Similar results were still obtained after adjusting for the relevant covariates (OR = 1.404; 95% CI, 1.008-1.954; P = 0.044). In subgroup analyses grouped by smoking status, higher VAI was associated with increased odds of developing ED only in the current smoking group (OR = 1.092; 95% CI, 1.021-1.167; P = 0.010).This study indicated that higher VAI is independently related to ED risk and that early intervention is necessary to reduce the progression of ED with high VAI levels.